2008
DOI: 10.1074/jbc.m802574200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Processes of Inhibition and Stimulation of ATP Synthase Caused by the Phytotoxin Tentoxin

Abstract: F 1 -ATPase is the smallest mechanical motor known. Tentoxin, a cyclic peptide produced by phytopathogenic fungi, inactivates the F 1 motor in sensitive plants at nanomolar to micromolar concentrations, whereas higher concentrations surpass the natural activity of the enzyme. Single molecule studies now have clarified the molecular steps involved in both processes. Inactivation delays the dwell time of a single step in the complete 360°turn and results in an asymmetric rotation of the central rotor subunit. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Structure of the Chloroplast c 14 Ring-The final model of the chloroplast c ring rotor consists of 14 identical protomers that are symmetrically arranged around a central pore (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Structure of the Chloroplast c 14 Ring-The final model of the chloroplast c ring rotor consists of 14 identical protomers that are symmetrically arranged around a central pore (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of spinach chloroplast F1 complexed with tentoxin illustrated that the catalytic site on the ␣␤ 1 dimer is in a closed conformation (Groth, 2002). Detailed experimental analysis shed light on the mechanism of tentoxin action and demonstrated that a single molecule of the toxin affects ADP release in a non-competitive manner (Meiss et al, 2008).…”
Section: Low Molecular Weight Toxic Secondary Metabolitesmentioning
confidence: 98%
“…However, the fact that the crystal structures identified so far are comparable with the reference structure implies that the crystallization of F 1 in the binding dwell state is very difficult. One possible way is to crystallize F 1 at low temperature (16) or F 1 inhibited by tentoxin (36), where it spends most of the catalytic turnover time pausing at the binding dwell angle.…”
Section: Discussionmentioning
confidence: 99%